White Pomegranate Extract Gel's Efficacy as A Teeth-Whitening Agent - Ige Frameski Radila Muga; Dinda Lathifah Rahmawati; Fauziah Rachmawati (International Journal Of Health Science, 2022)
Tooth discoloration is one of the most common concerns associated with dental appearance or cosmetic issues. Teeth whitening is one of the conservative procedures that may be utilized to overcome tooth discoloration (bleaching). Utilizing natural bleaching agents is a safer, less expensive, and more accessible option. Malic acid (malic acid) and elegat acid (allegic acid) obtained from fruits can be used to whiten teeth. White pomegranate (Punica granatum L.) is one of these all-natural components. The purpose of this research was to evaluate the efficacy of white pomegranate extract gel as a bleaching agent against tooth discoloration. This research utilizes an experimental laboratory design. There were 24 mandibular second premolars utilized as samples. All teeth were submerged for seven days in the coffee solution. Utilizing spectrophotometry, tooth discoloration was measured. After being soaked in a coffee solution and then a white pomegranate extract gel, the item was dried. Group 1: teeth soaked in white pomegranate extract gel with a concentration of 70%. Group 2: teeth soaked in white pomegranate extract gel with a concentration of 80%. Group 3: teeth soaked in white pomegranate extract gel with a concentration of 90%. Group 4: 10% carbamide peroxide gel as a positive control. Each specimen was immersed for 56 hours. Using a spectrophotometer, tooth discoloration was assessed following immersion in white pomegranate gel extract and carbamide peroxide gel. Based on the results of the LSD test, the % group was determined to be the most effective as a teeth whitening agent. White pomegranate extract gel has an influence on tooth discoloration and tooth whitening attempts.